Frequency of anti-Chlamydia trachomatis antibodies in infertile women referred to Tabriz Al-Zahra hospital - Mahtab Sattari; Mehdi Ghiami Rad; Aaliye Ghasemzadeh; Zahra Mohammadoghli Reihan (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Infertility is one of the major issues in society and its incidence is estimated to be almost 10-15%. Chlamydia trachomatis (C. trachomatis) is an important cause of sexually transmitted diseases leading to infertility. Objective: This study was designed to determine the frequency of anti-C. trachomatis antibodies in infertile women at Al-zahra hospital, Tabriz, Iran. Materials and Methods: In this cross-sectional study, the blood samples were collected randomly from 184 infertile women (case group) and 100 pregnant women (control group). The frequency of specific IgG and IgM anti-C. trachomatis antibodies were evaluated using ELISA method. Results: The frequency of IgG anti-C. trachomatis antibody in the control and case groups was 18% and 35.88%, respectively. IgM anti-C. trachomatis antibody was found in 2% of controls and 5.44% of infertile women. Our results showed the significant differences between the case and control groups in anti-C. trachomatis antibodies (IgG, p=0.035 and IgM, p=0.004). Also, no significant relation was seen between the frequency of anti-C. trachomatis antibodies and age, location, and tubal factor infertility in our two study groups. Conclusion: According to high frequency of antibody anti-C. trachomatis among infertile women in competition to the control group, evaluation and treatment of Chlamydia infections is necessary in these patients